2020
DOI: 10.1088/1755-1315/590/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Use of swab for DNA sampling from confiscated raptors for molecular sexing

Abstract: The objective of the study was to evaluate the feasibility and efficiency of using swab to collect tracheal and cloacal epithelial cells of confiscated raptor bird for genetic studies. Commercial swab kits were used to collect samples from 34 individuals of 10 raptor species, and as comparison blood samples from the same individual were also analyzed. FavorPrep™ Blood Genomic DNA Extraction Mini Kit dan FavorPrep™ Tissue Genomic DNA Extraction Mini Kit were used respectively to extract DNA from blood and epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The length of CHD1-W gene of straw-headed bulbul was shorter than its CHD-1-Z gene. This result was in accordance with previous studies which using the primer set of 2550F/2718R on different bird species in Indonesia, such as Bali starling (Leucopsar rothchildi) (Wirastika et al 2015), Maleo (Macrocephalon maleo) (Yuda & Saputra 2021), 9 bird of prey species (Yuda et al 2020), and 56 birds species of 13 families (Sulandari & Zein 2012). In contrary, using P2/P8 primer set for molecular sexing for two different species of bulbul (Pycnonotus spp), Pamulang & Hanyarto (2021) reported that the length of CHD1-W gene (400 bp) was longer than CHD1-Z (300 bp).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The length of CHD1-W gene of straw-headed bulbul was shorter than its CHD-1-Z gene. This result was in accordance with previous studies which using the primer set of 2550F/2718R on different bird species in Indonesia, such as Bali starling (Leucopsar rothchildi) (Wirastika et al 2015), Maleo (Macrocephalon maleo) (Yuda & Saputra 2021), 9 bird of prey species (Yuda et al 2020), and 56 birds species of 13 families (Sulandari & Zein 2012). In contrary, using P2/P8 primer set for molecular sexing for two different species of bulbul (Pycnonotus spp), Pamulang & Hanyarto (2021) reported that the length of CHD1-W gene (400 bp) was longer than CHD1-Z (300 bp).…”
supporting
confidence: 92%
“…In addition, for endangered species, it can be difficult to obtain research permits for more intrusive sampling methods. As an alternative, biological samples such as feather, buccal cells, faecal matter and post-hatched egg-shell membrane can be collected in the field with minimal disturbance to the species's study Wirastika et al 2015;Yuda & Saputra 2021;Yuda et al 2020;Ushine et al 2016).…”
mentioning
confidence: 99%
“…As an alternative to invasive sampling, researchers have adopted noninvasive sampling methods such as DNA capture from molted feathers 8,9 , feces 10,11 , and egg shell membrane 12,13 . In addition the application of moderately invasive sampling such as buccal swabs 14,15 has also increased.…”
Section: Introductionmentioning
confidence: 99%